Cyanidin-3-O-glucoside plays a protective role against renal ischemia/ reperfusion injury via the JAK/STAT pathway - Yufeng Xiong; Jun Jian; Honglin Yu; Jiejun Wu; Hu Mao; Ruikang Feng; Lei Wang; Yonghong Jian; Xiuheng Liu (Acta Cirúrgica Brasileira, 2023)
ABSTRACT Purpose: To investigate the role of cyanidin-3-O-glucoside (C3G) in renal ischemia/reperfusion (I/R) injury and the potential mechanisms. Methods: Mouse models were established by clamping the left renal vessels, and in vitro cellular models were established by hypoxic reoxygenation. Results: Renal dysfunction and tissue structural damage were significantly higher in the I/R group. After treatment with different concentrations of C3G, the levels of renal dysfunction and tissue structural damage decreased at different levels. And its protective effect was most pronounced at 200 mg/kg. The use of C3G reduced apoptosis as well as the expression of endoplasmic reticulum stress (ERS)-related proteins. Hypoxia/reoxygenation (H/R)-induced apoptosis and ERS are dependent on oxidative stress in vitro. In addition, both AG490 and C3G inhibited the activation of JAK/STAT pathway and attenuated oxidative stress, ischemia-induced apoptosis and ERS. Conclusions: The results demonstrated that C3G blocked renal apoptosis and ERS protein expression by preventing reactive oxygen species (ROS) production after I/R via the JAK/STAT pathway, suggesting that C3G may be a potential therapeutic agent for renal I/R injury.